EKSISTENSI TRADISI BESAOH PADA MASYARAKAT PETANI DI DESA TELAK, KECAMATAN PARITTIGA, KABUPATEN BANGKA BARAT - Putri Tanjung, Aulia (Profesional Muda Cendekia Publishing, 2023)
This study aims to explain the Besaoh tradition carried out by the people of Bangka, especially West Bangka, namely in Telak Village. This research also aims to find out how the community maintains the besaoh tradition in the midst of a community where some have abandoned this tradition. However, the people of Telak Village still apply the Besaoh tradition in land management and harvesting. To analyze the problems of this research, the authors use the theory of Functionalism and Reciprocity by Malinowski. The research method used is a qualitative approach with descriptive qualitative research, and the informant selection technique is a purposive sampling technique with a total of 10 informants. Sources of research data come from primary and secondary data. Primary data was obtained through observation and interviews with farmer actors who still practice besaoh and also traditional leaders as cultural observers in the community. Secondary data obtained through documentation and literature study. The results of the research show that farming communities who still carry out the besaoh tradition are seen through the view of functionalism theory, the besaoh tradition is very beneficial to these farming communities. The system of providing labor assistance when farming takes turns is called the principle of reciprocity or reciprocity. The besaoh tradition in the farming community in Telak Village, West Bangka Regency, still functions as follows: (1). Economic Function; (2). The function of social relations, such as culture which is a necessity in certain events in the community in Telak Village, the besaoh tradition in which the community strengthens friendship ties and strengthens unity and shared values, the nature of sharing and the besaoh tradition which has local wisdom values.